2010
DOI: 10.1002/jcb.22527
|View full text |Cite
|
Sign up to set email alerts
|

Src‐like adaptor protein regulates osteoclast generation and survival

Abstract: Src-like adaptor protein (SLAP) is a hematopoietic adaptor containing Src homology (SH)3 and SH2 motifs and a unique carboxy terminus. Unlike c-Src, SLAP lacks a tyrosine kinase domain. We investigated the role of SLAP in osteoclast development and resorptive function. Employing SLAP-deficient mice, we find lack of the adaptor enhances in vitro proliferation of osteoclast precursors in the form of bone marrow macrophages (BMMs), without altering their survival. Furthermore, osteoclastogenic markers appear more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…Shortly thereafter, Pakuts et al confirmed by Far Western analysis that SLAP2 directly associates with CSF-1R both before and after CSF-1 stimulation [46]. Notably, SLAP also bound CSF-1R [17,46], but in contrast to the constitutive association of SLAP2 with CSF-1R, SLAP interaction was strongly induced by CSF-1 stimulation [46]. This suggests that the molecular basis of the interaction between CSF-1R and SLAP or SLAP2 may differ.…”
Section: Csf-1rmentioning
confidence: 71%
See 4 more Smart Citations
“…Shortly thereafter, Pakuts et al confirmed by Far Western analysis that SLAP2 directly associates with CSF-1R both before and after CSF-1 stimulation [46]. Notably, SLAP also bound CSF-1R [17,46], but in contrast to the constitutive association of SLAP2 with CSF-1R, SLAP interaction was strongly induced by CSF-1 stimulation [46]. This suggests that the molecular basis of the interaction between CSF-1R and SLAP or SLAP2 may differ.…”
Section: Csf-1rmentioning
confidence: 71%
“…SLAP mRNA is predominantly expressed in lymphoid tissues, including spleen, thymus, and lymph nodes, and is expressed in both primary T cells and primary B cells [16]. High levels of SLAP mRNA expression have also been detected in lung, fetal brain, and epithelial intestine, while moderate levels were detected in heart, adult brain, liver, skeletal muscle, kidney, placenta, pancreas, skin, and bone marrow macrophages [4,5,[17][18][19]. SLAP is expressed in a number of cell lines, including NIH3T3 fibroblasts [20], BaF3 pro-B cells [18], and P815 mastocytoma cells [21], and its expression can be induced in myeloidderived cell lines U937, HL60, and NB-4 by stimulation with all-trans retinoic acid [22].…”
Section: Slap and Slap2 Expressionmentioning
confidence: 94%
See 3 more Smart Citations